Chondroitin Sulfate and Fucosylated Chondroitin Sulfate as Stimulators of Hematopoiesis in Cyclophosphamide-Induced Mice - Nadezhda E. Ustyuzhanina; Natalia Yu. Anisimova; Maria I. Bilan; Fedor V. Donenko; Galina E. Morozevich; Dmitriy V. Yashunskiy; Anatolii I. Usov; Nara G. Siminyan; Kirill I. Kirgisov; Svetlana R. Varfolomeeva; Mikhail V. Kiselevskiy; Nikolay E. Nifantiev (Pharmaceuticals, 2021)
The immunosuppression and inhibition of hematopoiesis are considered to be reasons for the development of complications after intensive chemotherapy and allogeneic hematopoietic stem cell transplantation. Chondroitin sulfate (CS), isolated from the fish Salmo salar, and fucosylated chondroitin sulfate (FCS), isolated from the sea cucumber Apostichopus japonicus, were studied for their roles as stimulators of hematopoiesis in a model of cyclophosphamide-induced immunosuppression in mice. The recombinant protein r G-CSF was applied as a reference. The studied polysaccharides were shown to stimulate the release of white and red blood cells, as well as platelets from bone marrow in immunosuppressed mice, while r G-CSF was only responsible for the significant increase in the level of leucocytes. The analysis of different populations of leucocytes in blood indicated that r G-CSF mainly stimulated the production of neutrophils, whereas in the cases of the studied saccharides, increases in the levels of monocytes, lymphocytes and neutrophils were observed. The normalization of the level of the pro-inflammatory cytokine IL-6 in the serum and the recovery of cell populations in the spleen were observed in immunosuppressed mice following treatment with the polysaccharides. An increase in the proliferative activity of hematopoietic cells CD34(+)CD45(+) was observed following ex vivo polysaccharide exposure. Further study on related oligosaccharides regarding their potential as promising drugs in the complex prophylaxis and therapy of hematopoiesis inhibition after intensive chemotherapy and allogeneic hematopoietic stem cell transplantation seems to be warranted.